Multiple rare variants in different genes account for multifactorial inherited susceptibility to colorectal adenomas. - Fearnhead, N; Wilding, J; Winney, B; Tonks, S; Bartlett, S; Bicknell, D; Tomlinson, I; Mortensen, N; Bodmer, W (2004)
Clear-cut inherited Mendelian traits, such as familial adenomatous polyposis or hereditary nonpolyposis colorectal cancer, account for <4% of colorectal cancers. Another 20% of all colorectal cancers are thought to occur in individuals with a significant inherited multifactorial susceptibility to colorectal cancer that is not obviously familial. Incompletely penetrant, comparatively rare missense variants in the adenomatous polyposis coli gene, which is responsible for familial adenomatous polyposis, have been described in patients with multiple colorectal adenomas. These variants represent a category of variation that has been suggested, quite generally, to account for a substantial fraction of such multifactorial inherited susceptibility. The aim of this study was to explore this rare variant hypothesis for multifactorial inheritance by using multiple colorectal adenomas as the model. Patients with multiple adenomas were screened for germ-line variants in a panel of candidate genes. Germ-line DNA was obtained from 124 patients with between 3 and 100 histologically proven synchronous or metachronous adenomatous polyps. All patients were tested for the adenomatous polyposis coli variants I1307K and E1317Q, and variants were also sought in AXIN1 (axin), CTNNB1 (beta-catenin), and the mismatch repair genes hMLH1 and hMSH2. The control group consisted of 483 random controls. Thirty of 124 (24.9%) patients carried potentially pathogenic germ-line variants as compared with 55 ( approximately 12%) of the controls. This overall difference is highly significant, suggesting that many rare variants collectively contribute to the inherited susceptibility to colorectal adenomas.